Compassion-focused therapy (CFT) for the reduction of the self-stigma of mental disorders: the COMpassion for Psychiatric disorders, Autism and Self-Stigma (COMPASS) study protocol for a randomized controlled study - M. Riebel; O. Rohmer; E. Charles; F. Lefebvre; S. Weibel; L. Weiner (Trials, 2023)
Abstract Background People with mental disorders face frequent stigmatizing attitudes and behaviors from others. Importantly, they can internalize such negative attitudes and thus self-stigmatize. Self-stigma is involved in diminished coping skills leading to social avoidance and difficulties in adhering to care. Reducing self-stigma and its emotional corollary, shame, is thus crucial to attenuate the negative outcomes associated with mental illness. Compassion-focused therapy (CFT) is a third-wave cognitive behavioral therapy that targets shame reduction and hostile self-to-self relationship and allows for symptom improvement while increasing self-compassion. Although shame is a prominent part of the concept of self-stigma, the efficacy of CFT has never been evaluated in individuals with high levels of self-stigma. The purpose of this study is to evaluate the efficacy and acceptability of a group-based CFT program on self-stigma, compared to a psychoeducation program for self-stigma (Ending Self-Stigma) and to treatment as usual (TAU). We hypothesize that diminished shame and emotional dysregulation and increased self-compassion will mediate the relationship between self-stigma improvements post-therapy in the experimental group. Methods This seven-center trial will involve 336 participants diagnosed with a severe mental illness and/or autism spectrum disorder and reporting high levels of self-stigma. Participants will be randomized into one of three treatment arms: 12 week-treatment of compassion-focused therapy (experimental arm), 12 week-treatment of Psychoeducation (active control arm), and TAU (treatment as usual—passive control arm). The primary outcome is the decrease of self-stigma scores on a self-report scale, i.e., ISMI, at 12 weeks. Secondary endpoints include sustainability of self-stigma scores (ISMI) and self-reported scores regarding target psychological dimensions, e.g., shame and emotional regulation, social functioning, and psychiatric symptoms. Assessments are scheduled at pretreatment, post-treatment (at 12 weeks), and at 6-month follow-up. Acceptability will be evaluated via (i) the Credibility and Expectancy Questionnaire at T0, (ii) the Consumer Satisfaction Questionnaire for Psychotherapeutic Services posttreatment and at 6-month follow-up, (iii) attendance, and (iv) dropout rates. Discussion This study will evaluate the potential efficacy and acceptability of a group-based CFT program on the decrease of self-stigma and thereby contribute to the continuing development of evidence-based therapeutic interventions for the internalized stigma of mental and neurodevelopmental disorders. Trial registration ClinicalTrials.gov NCT05698589. Registered on January 26, 2023